Effects of Broodstock Age and Sperm Collection Time over a Natural Spawning Period on Sperm Cryopreservation in Farmed Greenlip Abalone, Haliotis laevigata. Issue 6 (14th December 2015) - Liu, Yibing; Li, Xiaoxu; Xu, Tong; Robinson, Nicholas; Qin, Jianguang
ABSTRACT: This study investigated the effects of broodstock age (2‐ and 3‐yr‐old), and sperm collection time at the beginning, middle, and end of a natural spawning period, on the ability of sperm to tolerate cryopreservation in farmed greenlip abalone, Haliotis laevigata . The quality of sperm was assessed by motility, fertilization rate, plasma membrane integrity, mitochondrial membrane potential (MMP), and acrosome integrity (AI). The sperm collected at the middle of a natural spawning period had significantly higher quality than those collected at the beginning and the end of the spawning period in terms of plasma membrane integrity, MMP, and AI of fresh and post‐thaw sperm, post‐thaw sperm motility, and fertilization rate. No significant difference was found between 2‐ and 3‐yr‐old animals in most quality parameters evaluated. The results suggested that sperm collected during the middle of the spawning season should be used for cryopreservation. The efficiency of genetic improvement programs can be further enhanced by using sperm collected from 2‐yr‐old abalone which has a similar ability to tolerate cryopreservation as 3‐yr‐old counterparts.